2016
DOI: 10.7860/jcdr/2016/16645.7533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACP-CPP Chewing Gum and Natural Chewable Products on Plaque pH, Calcium and Phosphate Concentration

Abstract: Introduction: Numerous epidemiological studies have documented dental caries as the major public health problems throughout the world. It is gradually increasing in the underdeveloped and developing countries especially in children due to increasing popularity of refined sugars. Aim:The aim of the study was to evaluate the effect of natural chewable products (Tulsi, sesame seeds, fennel seeds, coconut) and ACP-CPP chewing gum on plaque pH, calcium and phosphate concentration. Materials and Methods:A randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Other studies tested the antibacterial effect of fennel seed methanolic extract against the cariogenic bacteria S. mutans, compared it with CHX 0.2%, and found that CHX was more effective and produced a more significant inhibition zone [27,28]. Furthermore, other researchers found that chewing the seeds for five minutes showed a rise in salivary pH that can prevent demineralization and have an anti-cariogenic property [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies tested the antibacterial effect of fennel seed methanolic extract against the cariogenic bacteria S. mutans, compared it with CHX 0.2%, and found that CHX was more effective and produced a more significant inhibition zone [27,28]. Furthermore, other researchers found that chewing the seeds for five minutes showed a rise in salivary pH that can prevent demineralization and have an anti-cariogenic property [29].…”
Section: Discussionmentioning
confidence: 99%
“…The O. sanctum group showed statistically significant rise in salivary pH after 5 and 30 min similar to other studies. [ 11 ] However, the exact mechanism of action is not known. It is shown that a food requiring a lot of chewing produces more copious salivary flow with an increased buffering capacity, thereby more effectively neutralizing plaque acids and aiding oral clearance of food debris.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] It has also shown significant increase in plaque pH after 5 min and 30 min of chewing leaves. [ 11 ] Some authors have suggested that O. sanctum can be recommended as an anticaries mouthwash in children after further research. [ 12 ] Though both the herbs are anti-cariogenic, there are no studies available about their potential in reversing the cariogenic effects of other foods.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest are reports that sesame oil can improve oral health by its use in a traditional Ayurvedic treatment, oil pulling, [123][124][125][126][127][128][129][130] and other oral hygiene approaches. [131][132][133] The practice of oil pulling involves swishing an oil around the mouth for a specified time and then spitting out the oil. Its purpose is to remove bacteria and improve oral health.…”
Section: Pain Managementmentioning
confidence: 99%